2017
DOI: 10.1080/09540105.2017.1328662
|View full text |Cite|
|
Sign up to set email alerts
|

Dual-labelled immunoassay with goldmag nanoparticles and quantum dots for quantification of casein in milk

Abstract: A dual-labelled immunoassay using goldmag nanoparticles (GMNPs) and CdTe quantum dots (QDs) was applied for the quantification of casein in milk. In this method, anti-casein monoclonal antibody bound to GMNPs was used as capture probe, and the anti-casein polyclonal antibody, labelled with CdTe QDs, was employed as detection probe. This dual-labelled immunoassay was optimized and applied in the testing of casein content of three brands of commercial milks. The results showed a good linear tendency between case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 32 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The difference in structure and content of casein in human milk and cow's milk is the main cause of casein sensitization. A study has shown that about 65% of sufferers are allergic to casein [86]. Whey protein accounts for 20% of milk protein, and the main allergenic components are α-lactalbumin and β-lactoglobulin [87].…”
Section: Milkmentioning
confidence: 99%
“…The difference in structure and content of casein in human milk and cow's milk is the main cause of casein sensitization. A study has shown that about 65% of sufferers are allergic to casein [86]. Whey protein accounts for 20% of milk protein, and the main allergenic components are α-lactalbumin and β-lactoglobulin [87].…”
Section: Milkmentioning
confidence: 99%